Enhanced photocatalytic generation of hydrogen by Pt-deposited nitrogen-doped TiO2 hierarchical nanostructures - Naik, Brundabana; Moon, Song Yi; Kim, Sang Hoon; Park, Jeong Young (ELSEVIER, 2015)
We report the photocatalytic activity of hydrogen generation on Pt nanoparticles deposited on hierarchically porous N-doped TiO2 nanostructures (Pt-NHPT). The photocatalysts are composed of Pt nanoparticles well dispersed throughout hierarchical macroporous TiO2 fibrous channels. The interstitial N doping extends light absorption toward the visible region. We found that the porosity of N-doped TiO2 nanostructures can be tuned using different annealing temperatures. While Pt-NHPT catalysts calcined at 300 degrees C (Pt-NHPT-300) have both macro- and mesoporosity, Pt-NHPT catalysts calcined at 800 degrees C (Pt-NHPT-800) exhibit only macroporosity. We found that Pt-NHPT-300 shows a two-fold higher H-2 evolution activity than that of Pt-NHPT-800, and 30% higher activity than undoped hierarchical catalysts (Pt-HPT-300). The enhanced photoactivity is attributed to the synergistic effects of N doping, hierarchical porosity, and charge transfer between the TiO2 nanostructures and the Pt co-catalyst. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ELECTRONIC-STRUCTURE; WATER; NANOPARTICLES; PT/TIO2; PT/GAN